Efficacy of an educational intervention on students' attitudes regarding spirituality in healthcare: a cohort study in the USA. Issue 4 (4th April 2019) - Smothers, Zachary Paul Wargo; Tu, Jennifer Young; Grochowski, Colleen; Koenig, Harold G
Abstract : Objective: To determine if an educational intervention focused on the role of spirituality in healthcare positively affects medical students' attitudes and perceptions relating to this topic. Design: A pre-post cohort study. Setting: An undergraduate medical institution affiliated with an academic medical center in the USA. Participants: A total of 110 medical students currently on their clinical rotations received the educational intervention, of whom 71 (65%) completed both the presurvey and postsurvey. Demographic variables did not significantly differ from the national average of medical students, or from a comparison group. All students who attended the intervention were given the opportunity to participate in the survey. Interventions: The educational intervention consisted of a 60-minute lecture focusing on religion/spirituality (R/S) in healthcare, followed by a 90-minute case discussion in a small group setting. Primary and secondary outcome measures: Assessment consisted of 18-item preintervention and postintervention survey quantifying student's attitudes towards, comfort with, and perceptions of R/S in healthcare. Results: Attitudes towards, comfort with, and perceptions of R/S in healthcare were generally positive preintervention. Following the intervention, students expressed an increased willingness to include R/S competency in their future practice (p=0.001), were more comfortable sharing their own R/S beliefs with a patient when appropriate (p=0.02), and were more willing to approach a patient with R/S concern (p=0.04). The other surveyed attitudes demonstrated positive, but non-significant improvement. Conclusion: An educational intervention focusing on approaching patients with R/S concerns has the ability to improve the attitudes and comfort of medical students. By incorporating a total of 150 minutes of education about R/S, medical schools can help develop this particular area of cultural competence, preparing a generation of physicians to professionally approach R/S concerns of patients. Future research should move beyond quantifying attitudes and strive to understand changes in knowledge and student behaviour.